Low birth weight predicts impaired cardiac structure and function in mid-adulthood. (14th October 2021) - Huynh, Q; Magnussen, C; Venn, A; Marwick, T
Abstract: Aims: We sought to determine the relationship of low birth weight (LBW) with adult cardiac structure and function and investigate potential causal pathways. Methods: We followed 925 Australians (41.3% male) from childhood (7–15 years) to young- (26–36 years) and mid-adulthood (36–50 years). Left ventricular (LV) global longitudinal strain (GLS, %), LV mass index (LVMi, g/m 2.7 ), LV filling pressure (E/e') and left atrial volume index (LAVi, g/m2) were measured by echocardiography in mid-adulthood. Birth weight category was self-reported in adulthood and classified as low (≤5 pounds or ≤2270 g), normal (5–8 pounds or 2271–3630 g) and high (>8 pounds or >3630 g). Results: 7.5% (69/925) reported LBW. Compared with participants with normal birth weight, those with LBW had a 2.01-fold (1.19–3.41, p=0.009) higher risk of impaired GLS (GLS >−18%) and 2.63-fold (0.89–7.81, p=0.08) higher risk of LV hypertrophy (LVMi >48 g/m 2.7 in men or >44 g/m 2.7 in women) in adulthood independent of age, sex and any measures of socioeconomic status. Participants with LBW significantly increased body fat from childhood to adulthood relative to their peers, which was associated with greater levels of triglycerides, fasting blood glucose and arterial stiffness in adulthood. These factors were the strongest mediators in the association of LBW with impaired GLS in adulthood and together, explained half of the LBW effect size. The remaining half of this association was independent of any measured factors. Conclusions: LBW was associated with impaired cardiac structure and function in mid-adulthood. This association was only partially explained by known risk factors. Funding Acknowledgement: Type of funding sources: None.